29.1k views
0 votes
Simplify
(6 + 3i)(6 − 3i)

2 Answers

1 vote

Answer:


\displaystyle 45

Explanation:


\displaystyle (6 + 3i)(6 - 3i) = 36 - 9i^2 = 36 - 9[-1] = 36 + 9 = 45

Extended Information on the Complex Number System


\displaystyle √(-1) = i \\ -1 = i^2 \\ -i = i^3 \\ 1 = 4\:[Any\:multiple\:of\:four]

I am joyous to assist you anytime.

User Cerissa
by
6.9k points
7 votes

Answer:

45

Explanation:

(6 + 3i)(6 − 3i) =6 (6 − 3i)+ 3i(6 − 3i)

= 36 -18i +18i-9
i^(2)

if
i^(2) =-1

36 -18i +18i-9
i^(2) = 36-9(-1)

=36+9

=45

=36-9i^2

=6^2 - (3i)^2

User LB Ben Johnston
by
5.4k points